2018
DOI: 10.1021/acs.jpcc.8b10770
|View full text |Cite
|
Sign up to set email alerts
|

Local Environment and Dynamic Behavior of Fluoride Anions in Silicogermanate Zeolites: A Computational Study of the AST Framework

Abstract: In silicogermanate zeolites containing double four-ring (d4r) building units, the germanium atoms preferentially occupy the corners of these cube-like units. While this general behaviour is well known, the absence of long-range order precludes a determination of the preferred arrangements of Si and Ge atoms at the corners of d4r cages by means of crystallographic methods. If fluoride anions are present during the synthesis, these are incorporated into the d4r cages. Due to the sensitivity of the 19 F chemical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(88 citation statements)
references
References 61 publications
14
74
0
Order By: Relevance
“…TheG ed istribution in AST germanosilicates was thoroughly investigated at the DFT level, focusing on the equilibrium locations of fluoride and its dynamic behaviour. [30] Theresults clearly demonstrated that the formation of Ge-O-Ge linkages is energetically favourable in the fluoridecontained AST,but in the absence of the fluoride anion, there are no clear trends in Ge-O-Ge and Ge-O-Si energetic preferences.T hese calculations thus showed the templating effect of F À leading to d4r units with Ge-O-Ge linkages in AST germanosilicates,i nl ine with the EXAFS study of UTL, [31] which showed Ge atoms at asingle face of (4Ge,4Si) d4r units.H owever,adifferent Ge distribution in d4r was found in ITQ-22 (IWW)a nd ITQ-13 (ITH)b yN MR. [32] Therefore,t he Ge distribution in d4r germanosilicates is likely governed by the flexibility of T-O-T linkages in d4r units which, is framework dependent, as previously shown at various levels of theory. [33] In ar ecent computational investigation, the stability ranges for Si-O-Si and Ge-O-Ge angles in pure silica and pure germania cristobalite were calculated based on aD FT analysis employing aperiodic model.…”
Section: Insight From Computational Investigationmentioning
confidence: 99%
“…TheG ed istribution in AST germanosilicates was thoroughly investigated at the DFT level, focusing on the equilibrium locations of fluoride and its dynamic behaviour. [30] Theresults clearly demonstrated that the formation of Ge-O-Ge linkages is energetically favourable in the fluoridecontained AST,but in the absence of the fluoride anion, there are no clear trends in Ge-O-Ge and Ge-O-Si energetic preferences.T hese calculations thus showed the templating effect of F À leading to d4r units with Ge-O-Ge linkages in AST germanosilicates,i nl ine with the EXAFS study of UTL, [31] which showed Ge atoms at asingle face of (4Ge,4Si) d4r units.H owever,adifferent Ge distribution in d4r was found in ITQ-22 (IWW)a nd ITQ-13 (ITH)b yN MR. [32] Therefore,t he Ge distribution in d4r germanosilicates is likely governed by the flexibility of T-O-T linkages in d4r units which, is framework dependent, as previously shown at various levels of theory. [33] In ar ecent computational investigation, the stability ranges for Si-O-Si and Ge-O-Ge angles in pure silica and pure germania cristobalite were calculated based on aD FT analysis employing aperiodic model.…”
Section: Insight From Computational Investigationmentioning
confidence: 99%
“…First of all, it needs to be emphasised that the DFT results depend on various parameters in the computational setup, especially the choice of exchangecorrelation functional and dispersion correction. While the PBE-D3 functional has been successfully used in studies of host-guest interactions between zeolites and organics, [79][80][81] it also has some known deficiencies. 82 As a consequence, the E zg values calculated with this method cannot be considered ''accurate'' in a quantitative sense, but they can still serve as reference values to gauge whether the force field calculations give reasonable trends.…”
Section: Assessing Force Field Performance Ii: Dft Calculationsmentioning
confidence: 99%
“…Therefore, it was assumed that all TMA molecules have the same orientation, preserving the body-centering of the structure and leading to 4 ̅ symmetry (Figure 1). 65 The situation is different for the QNU cation, which has a dipole moment. An essentially random orientation of the QNU molecules would require the use of a large supercell, and an identical orientation of all molecules (which would preserve the body-centering) would lead to an overall polarisation, which appears unlikely.…”
Section: Structure Modelsmentioning
confidence: 99%
“…57,58,[62][63][64] In a previous investigation by one of us, DFT structure optimisations and DFT-based ab-initio molecular dynamics (AIMD) calculations were used to study the local environment and fluoride dynamics in AST-type germanosilicates. 65 It was found that the fluoride anions reside at the cage centre in the pure end members SiO2-AST and GeO2-AST, but that they are displaced towards one Ge atom, or towards Ge-O-Ge edges, in mixed (Si,Ge)O2 systems, often forming directional Ge-F bonds with a length of 2.2 to 2.4 Å. The formation of these bonds leads to a reduction in the freedom of motion that is clearly visible in the root mean square displacements (RMSDs) of fluoride, and in the F-Ge radial distribution functions (RDFs).…”
Section: Introductionmentioning
confidence: 99%